Biological management of cowpea web blight incited by Rhizoctonia solani - PRIYANKA,; GODARA, S L; YADAV, SURESH; MATHUR, A C; MEENA, ANAND KUMAR (The Indian Journal of Agricultural Sciences, 2021)
Among the diseases of cowpea, web blight caused by Rhizoctonia solani Kuhn is the most serious soil borne disease which causes severe yield loss. A field trial was conducted during kharif 2016 to manage web blight disease of cowpea at ARS field of SKRAU, Bikaner. Combination of T. harzianum plus B. subtilis used as seed treatment (5 + 5 g/kg) and soil application (5+5 kg/ha) proved to be most effective against web blight incited by R. solani in field conditions and provided maximum disease control (79.5%). Seed emergence, plant survival, fresh and dry weight, root and shoot lengths and grain yield was higher and per cent cowpea plant mortality was lower in treatment T. harzianum plus B. subtilis used in combination as seed treatment (5 + 5 g/kg) and soil application (5 + 5 kg/ha). The bioagents used in the present investigation could be therefore, used as a part of integrated disease management (IDM) strategy for web blight of cowpea in areas where the disease is reported to cause substantial yield losses.